HEALTH AND HEALTH PLANNING OF THE NORTH SUMATRA REGIONAL POLICE IN THE EFFORT TO ACCELERATE THE NATIONAL COVID-19 VACCINATION PROGRAM IN 2021 - Dewi Mirakirana; Sri Melda Br Bangun (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2022)
Corona virus is a group of corona viruses that attack humans, where the disease was originally discovered in Wuhan and arrived in Indonesia at the end of 2019. To reduce the number of Covid-19 transmission, the Indonesian government is trying its best, one of which is by holding mass vaccinations organized by the government. Biddokkes in this case is in charge of implementing the acceleration of the national covid-19 vaccination program, carrying out several work steps, such as implementing planning. The planning of Biddokkes Polri consists of the members of the National Police with their respective ranks and terms of work.